Ozone-induced chemiluminescence of uranine in the presence of blood plasma - Zinchenko, V.D.; Gorіacha, I.P.; Golovina, K.N.; Kiriyenko, A.N.; Topchiy, I.I. (Reports of the National Academy of Sciences of Ukraine, 2017)
Chemiluminescent response of the "uranine-blood plasma" system to the effect of ozone consists of two parts, i.e. a gentle flash lasting about 5 seconds and the afterglow, falling within 20-30 min. The short burst is explained by chemiluminescence at the direct oxidation of uranine with ozone, and the long afterglow is done by the energy transfer to uranine from other reactive species. The action of hydrogen peroxide or a hydroxyl radical on the system in the process of afterglow does not influence its intensity. Hence, the conclusion is made that the transfer of energy to uranine is derived from singlet oxygen. However, it does not rule out the possibility of the afterglow by the triggering of other reactions under the influence of ozone, whose mechanism requires a further research.